PELATIHAN MEMBUAT PIGURA 3 DIMENSI PADA SISWA TUNAGRAHITA DI SLB YP3LB MAKASSAR - Bastiana, Bastiana; St. Kasmawati; Salsabila, Ika Putri; Agriani, Intan; Sahriati (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Learning life skills and simple skills is very important to provide provisions for mentally retarded students. The aims of this training are to provide simple skills in making three-dimensional frames for independent living. This activity is followed by 12 middle class students at SLB YP3LB Makassar. The paper uses a qualitative approach by making observations. The implementation of the training on making three-dimensional frames went smoothly and resulted in several examples of frames made by students. Training for mentally retarded students and other students with special needs requires hand-eye coordination and longer time to get neat skill results. For this reason, it is suggested to the teacher to train the coordination of fine motor movements of students so that the coordination of the eyes and hands of students is well formed.